2023
DOI: 10.1101/2023.09.05.556435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics and quantitative contribution of the aminoglycoside 6′-N-acetyltransferase type Ib [AAC(6′)-Ib] to amikacin resistance

Ophélie d’Udekem d’Acoz,
Fong Hue,
Tianyi Ye
et al.

Abstract: Aminoglycosides are essential components in the available armamentarium to treat bacterial infections. The surge and rapid dissemination of resistance genes strongly reduce their efficiency, compromising public health. Among the multitude of modifying enzymes that confer resistance to aminoglycosides, the aminoglycoside acetyltransferase AAC(6′)-Ib is the most prevalent and relevant in the clinical setting as it can inactivate numerous aminoglycosides, such as amikacin. Although the mechanism of action, struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…1A and Table 1). However, recent work revealed that some bacterial strains produce AAC(6′)-Ib in quantities far exceeding those needed for clinical resistance [16, 31]. This finding highlights the necessity for an inhibitor with enough potency to effectively combat a range of pathogenic bacteria, even in environments with high enzyme concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…1A and Table 1). However, recent work revealed that some bacterial strains produce AAC(6′)-Ib in quantities far exceeding those needed for clinical resistance [16, 31]. This finding highlights the necessity for an inhibitor with enough potency to effectively combat a range of pathogenic bacteria, even in environments with high enzyme concentrations.…”
Section: Introductionmentioning
confidence: 99%